PRODUCTION SHARING CONTRACT: IS IT WITHIN PRIVATE OR PUBLIC DOMAIN? - Purba, Achmad Zen Umar (UI Scholars Hub, 2021)
Investment is always requires government attention including on the oil sector. Production Sharing Contract (PSC) is an agreement constitutes the regime of utilizing the interest of state is constitutionally used to the greatest possible extent for the prosperity of the people. PSC is part of Foreign Direct Investment (FDI) since it involves the private equity of foreign investors. Thus, PSC in one hand is a private contract and it belongs to the private domain, in the other hand, state as the owner of natural resources is act as a party in this business transaction. This paper discusses Production Sharing Contract, whether it is in private or public domain.